(untitled) (SCIÉNDO INGENIUM, 2023)
Organizations incur economic losses due to the failure of Traditional Information Technology (IT) management, which requires the implementation of more efficient technologies such as Artificial Intelligence. The objective of this research was to implement a Prototype of Virtual Personal Assistant based on Artificial Intelligence applied in IT offices of the Public Sector, in order to assist IT leaders in Project Management. It was carried out in three stages: General review of the IT project management process, design and implementation of the prototype, and evaluation of the developed prototype. As a result, a prototype was implemented, developed with the Python programming language, on a Microsoft Windows 10 platform, which interacts with voice and natural language and fulfills three functions: Creation of an IT Project, Generate a record of queries and observations of suppliers under market study, Generate Selection Committee record. The prototype assists the IT leader in Project management, simplifying and optimizing time and resources in the activities of organizing, capturing and recording information on IT Projects in the IT Offices of Public Sector organizations.